2018
DOI: 10.3389/fgene.2018.00387
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Analysis With a 50K Transcribed Gene SNP-Chip Identifies QTL Affecting Muscle Yield in Rainbow Trout

Abstract: Detection of coding/functional SNPs that change the biological function of a gene may lead to identification of putative causative alleles within QTL regions and discovery of genetic markers with large effects on phenotypes. This study has two-fold objectives, first to develop, and validate a 50K transcribed gene SNP-chip using RNA-Seq data. To achieve this objective, two bioinformatics pipelines, GATK and SAMtools, were used to identify ~21K transcribed SNPs with allelic imbalances associated with important a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
102
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(108 citation statements)
references
References 49 publications
6
102
0
Order By: Relevance
“…Fish population, marker density, LD, and size of adjacent SNP windows may, partially, explain the discrepancies in the results obtained from the different studies. In addition, SNPs used in the current study were identified from fish families of extreme phenotypes and thus, perhaps, are more informative for the current GWA analysis [19]. In agreement with previous GWA studies, growth is multifactorial in nature, and growth-related genes regulate development, cell proliferation, energy metabolism, and growth [89,104].…”
Section: Single Marker Association Analysissupporting
confidence: 73%
See 4 more Smart Citations
“…Fish population, marker density, LD, and size of adjacent SNP windows may, partially, explain the discrepancies in the results obtained from the different studies. In addition, SNPs used in the current study were identified from fish families of extreme phenotypes and thus, perhaps, are more informative for the current GWA analysis [19]. In agreement with previous GWA studies, growth is multifactorial in nature, and growth-related genes regulate development, cell proliferation, energy metabolism, and growth [89,104].…”
Section: Single Marker Association Analysissupporting
confidence: 73%
“…In this study, a 50K SNP chip was used to identify genomic regions associated with bodyweight gain, based on 50 SNP sliding windows and single-marker association analysis. Since the chip contains SNPs potentially associated with the bodyweight [16,19], the fish used in building the SNP-chip were not used for the current GWA analyses.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations